Coating of cochlear implant electrodes with bioactive DNA-loaded calcium phosphate nanoparticles for the local transfection of stimulatory proteins. (September 2021) - Wey, Karolin; Schirrmann, Ronja; Diesing, Detlef; Lang, Stephan; Brandau, Sven; Hansen, Stefan; Epple, Matthias
Abstract: Calcium phosphate nanoparticles were loaded with nucleic acids to enhance the on-growth of tissue to a cochlear implant electrode. The nanoparticle deposition on a metallic electrode surface is possible by electrophoretic deposition (EPD) or layer-by-layer deposition (LbL). Impedance spectroscopy showed that the coating layer did not interrupt the electrical conductance at physiological frequencies and beyond (1–40, 000 Hz). The transfection was demonstrated with the model cell lines HeLa and 3T3 as well as with primary explanted spiral ganglion neurons (rat) with the model protein enhanced green fluorescent protein (EGFP). The expression of the functional protein brain-derived neurotrophic factor (BDNF) was also shown. Thus, a coating of inner-ear cochlear implant electrodes with nanoparticles that carry nucleic acids will enhance the ongrowth of spiral ganglion cell axons for an improved transmission of electrical pulses.